1992
DOI: 10.1182/blood.v80.10.2643.2643
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygosity in a complete erythrocyte bisphosphoglycerate mutase deficiency

Abstract: Erythrocyte bisphosphoglycerate mutase (BPGM) deficiency is a rare disease associated with a decrease in 2,3-diphosphoglycerate concentration. A complete BPGM deficiency was described in 1978 by Rosa et al (J Clin Invest 62:907, 1978) and was shown to be associated with 30% to 50% of an inactive enzyme detectable by specific antibodies and resulting from an 89 Arg-->Cys substitution. The propositus' three sisters exhibited the same phenotype, while his two children had an intermediate phenotype. Samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…The first mutation was an arginine to cysteine mutation at amino acid 89 (corresponding to a C!T substitution at nucleotide 413); the second mutation was a frame shift mutation. Analysis of the propositus' children showed only the presence of the 89 Arg!Cys mutation [5]. The parents of the propositus were deceased and thus could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first mutation was an arginine to cysteine mutation at amino acid 89 (corresponding to a C!T substitution at nucleotide 413); the second mutation was a frame shift mutation. Analysis of the propositus' children showed only the presence of the 89 Arg!Cys mutation [5]. The parents of the propositus were deceased and thus could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The three exons of the BPGM gene were amplified from genomic DNA obtained from peripheral blood leukocytes using the polymerase chain reaction (PCR). Exons 1 and 2 were amplified using the primers described by Lemarchandel et al [5], with an annealing temperature of 56 C for exon 1 and of 52 C for exon 2. Exon 3 was amplified using 5 0 -TGATGTAGCA-CTTGCTGTG-3 0 and 5 0 -GTGAACTACTGATTAG-AATAGTG-3 0 , with a 55 C annealing temperature, giving a 762-bp fragment.…”
Section: Methodsmentioning
confidence: 99%
“…Fresh blood was collected in tubes containing EDTA. DNA was extracted from leucocytes and prepared using standard techniques (Lemarchandel et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…The coding regions, intron-exon boundaries, promoter and small introns, of the PK gene were amplified using four sets of oligonucleotides for 30 cycles (948C for 1 min, 55-678C for 1 min and 728C for 1 min 30 s with 1-2 mM MgCl 2 ) ( Fig 1, Table I). Single-stranded DNA was obtained by an asymmetric PCR reaction using similar conditions (60 cycles with a primer ratio of 50 : 2) (Lemarchandel et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…A complete deficiency of DPGM was discovered in a man of French origin associated with a moderate erythrocytosis. Sequence studies of this individual indicated heterozygosity with a cytidine to thymine substitution at nucleotide 413 and another heterozygosity with the deletion of cytidine at nucleotide 205 or 206 [93]. Therefore, the complete enzyme deficiency resulted from a genetic compound with one allele coding for a missense mutation (Arg to Cys at 89) and the other bearing a frameshift and premature termination of translation.…”
Section: Other Enzyme Deficiencies With Defined Molecular Defectsmentioning
confidence: 95%